Design of Inductive Power Transfer (IPT) for Low-Power Application - Muhammad Asri, Zainal Abidin; Wan Ismail, Ibrahim; M. S., Jadin (Asian Research Publishing Network (ARPN), 2015)
Inductive power transfer (IPT) is preferred for numerous applications nowadays, ranging from microwatt bio-engineering devices to high power battery charging system. IPT system is based on the basic concept of electromagnetics induction which able to transfer the power from a source of electrical to the load without using any type of physical interconnection. This paper present a low-cost designed and implementation of IPT system via magnetic resonant coupling. NI Multisim 14.0 software was used to simulate the circuit diagram and the hardware prototype was developed for testing.